Analysis of the relationship between organizational commitment and counter productive work behaviour on academicians - Baysal, Canan; Mısırdalı Yangil, Fulya; Sevim, Şerafettin (Serbian Journal of Management, 2020)
This study investigates the relationship between counter productive work behavior and organizational commitment which is one of the problems that organizations frequently face with in recent years. The relationship between affective commitment, normative commitment and continuance commitment from organizational commitment dimensions and abuse, production deviance, sabotage, theft and withdrawal from counter productive work behavior are examined one by one. The study has been conducted with the participation of 219 academic staff working at Dumlupınar University. In the study, a correlation analysis is performed to determine the relationship between the variables. Furthermore, Kruskal-Wallis H and Mann-Whitney U tests are conducted to determine their association with demographic variables. As a result of the analyses this study detects that affective commitment and normative commitment dimensions have negative direction and significant relationship with the withdrawal and abuse dimensions. Additionally, the negative direction and significant relationships are found between continuance commitment and withdrawal, abuse, theft dimension.